Analysis of The Implementation of The ISO 14001:2015 Environmental Management System at Manufacture Industry - Budi Prasetyo Samadikun; Himawan Aziz Muftiansyah; Nani Anggraini (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
ISO 14001:2015 is an international standard issued by the International Organization for Standardization that regulates Environmental Management Systems (EMS) to help companies manage environmental impacts, comply with regulations, and achieve continuous improvement. Manufacture Industry, a foreign investment company engaged in diesel engine production, implements EMS as part of its commitment to environmental sustainability. This study evaluates the implementation of ISO 14001:2015 by comparing each clause of the standard with actual operational practices within the company. Data were collected through field observations and document reviews. The results show that Manufacture Industry has effectively implemented all clauses of ISO 14001:2015, particularly in waste management, air quality monitoring, and regulatory compliance. However, improvements are still needed in increasing employee awareness regarding the use of PPE in high-risk work areas. This study provides a more practical and structured approach to EMS evaluation by integrating clause-based ISO assessment with real industrial practices, which can serve as a reference for industries in improving EMS performance and operational control.